Analysis of price variations and red chili market integration in Ciamis regency - Hendro, Nanang; Rahayu, Endang Siti; Fajarningsih, Rhina Uchyani (Linguistics and Culture Review, 2022)
Market integration can show that no matter what changes occur in the consumer market, it will cause price changes in the producer market. However, price information that has not been properly channeled between consumer and producer markets makes asymmetrical trasnmission and unintegrated market. This study aims to analyze the level of price variation and market integration of red chili in Ciamis Regency. The coefficient of variation analysis is used to analyze the level of price variation and the Johansen cointegration approach with the Vector Autoregression (VAR) / Vector Error Correction Model (VECM) model to analyze market integration. The results showed that the price fluctuation of red chili at the producer and consumer level was high and unstable. The results of the analysis of market integration show that there is market integration between the producer market and the consumer market in the long run but in the short term, they adjust to each other in the long term.